(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the communication strategies used in resolving organizational conflicts during the Branch Conference (Konfercab) of PC PMII Jombang in 2025. This research uses a qualitative approach with a field study type of research. Data collection techniques are carried out through in-depth interviews, observation, and documentation of the parties involved in the Konfercab PC PMII Jombang process. The data obtained is analyzed using qualitative data analysis techniques through the stages of data reduction, data presentation, and drawing conclusions. The research results show that the conflicts that arose during the 2025 PC PMII Jombang Conference were related to technical conflicts and procedural conflicts that occurred during the forum’s implementation. The communication strategies used to resolve these conflicts included dialogical communication, deliberation, persuasive approaches, and the role of mediators from the organization’s leaders to bridge differences in interests among members. These strategies were considered effective in easing tension, opening up space for constructive discussion, and maintaining organizational stability and solidarity after the conference. This research is expected to contribute to the development of organizational communication studies, especially in conflict management within student organizations, and serve as a reference for PMII members in handling organizational conflicts in a communicative, democratic, and constructive way.